Preseason aerobic physiological characteristics in Bosnia and Herzegovina professional football players - Kafedžic, E.; Covic, N.; Jeleškovic, E.; Alic, H.; Ibrahimovic, M.; Talovic, M. (Homosporticus, 2018)
Aim of the study was to investigate and quantify initial pre-season aerobic physiological characteristics (VO2max and AT) in Bosnia and Herzegovina professional football players. Additionally, the authors examined differences in aerobic characteristic by playing positions. Sample of 39 male football players (23.5 ± 4.6 yrs, 182.0 ± 5.6 cm, 77.8 ± 5.8 kg) playing for two best teams in BiH Premier league were subject to maximal incremental treadmill run on two separate occasions. No changes were observed for VO2max in players. Relative oxygen uptake at anaerobic threshold was lower in forwards compared to wide midfielders by 6.8 ml/kg/min (p = 0.033) Running velocity at anaerobic threshold was lower in CM in comparison to WM by 1.6 km/h (p = 0.037). Central defenders were higher compared to WB for 8 cm (p = 0.020) CM for 6.4 cm (p = 0.042), WM for 9.3 cm (p = 0.014) and F for 6.5 cm (p = 0.056). Central defenders` weight was significantly higher compared to WB for 7 kg (p = 0.053). Study provides aerobic power characteristics before preseason in football players and differentiation by playing positions. The findings from relatively low number of subjects indicate that BiH professional players have low VO2max compared to the elite standards which is insufficient to perform at professional level. Study reveled that differences among playing positions in aerobic capacity do not exist, with central midfielder being inferior to other players. Coaches can use results to create training programs to meet football specifics in terms of aerobic physiological demands.